PROSPECTING the Moon: Numerical simulations of temperature and sublimation rate of a cylindric sample. (May 2019) - Formisano, M.; De Sanctis, M.C.; De Angelis, S.; Carpenter, J.D.; Sefton-Nash, E.
Abstract: The goal of the ESA Luna 27/PROSPECT instrument [1] is to extract and characterize a regolith sample from the lunar south polar region, investigating its physical and chemical properties. The main target is to characterize the abundance and distribution of water ice and other volatiles so the challenge is to preserve volatiles in samples during the drilling transfer and analysis. In this work we provided numerical simulations in order to predict the expected ice sublimation rates and inform the system's development. Simulations are characterized by different initial boundary conditions as well as thermodynamic parameters and carried out on a cylinder representing a lunar regolith sample of the south polar region. Highlights: We applied a 3-D thermal modeling to a lunar south pole sample which combines the heat transfer and gas diffusion equations. We predicted water ice sublimation rates and surface temperatures. The results of this paper can be used not only for the ESA PROSPECT mission but also the lunar community.